Shear Tensile And Flexural Performance Of Sandwich Composite With Hexagonal Cell Wood Core Variation - Yaakob, Mohd Yuhazri; Amir Mohamed, Kamarul; Mohd Noh, Mohd Syahrin Amri; Husin, Mohd Amirhafizan; Tan, Teng Teng; Tan, Rui Jie; Pieter, Hasoloan Haery Ian (World Academy of Research in Science and Engineering, 2020)
Current industry demands product with better sustainability and efficiency in terms of weight. This particular demand can be met with introduction of lightweight materials with renewable sources. This article presents a study of sandwich composite with different honeycomb wood core variants and suggests a direction for future development. Six types of sandwich composites, made with rubber wood (RW), pine wood (PW), balsa wood (BW), honeycomb rubber wood (HRW), honeycomb pine wood (HPW), and honeycomb balsa wood (HBW) implemented with hexagonal cells together with glass fibre reinforced polymer skins are studied. Shear tensile and flexural performance of sandwich composites are tested according to ASTM standards. The results reveal that HRW core sandwich composite exhibits good flexural strength amongst the sandwich composite tested while having a proper weight reduction of about 513.92 kg/m3 compared to solid wood cores. It was also found that, the implementation of hexagonal cells in the wood cores increases the shear tensile performance of the sandwich composites. The results provided may facilitate future applications improvement as well as sustainability development